Управління платоспроможністю підприємства за матеріалами ТОВ «Кондитерський цех» - Кутузова, Ірина Олександрівна; Kutuzova, Iryna Oleksandrivna (Ірпінь, 2023)
Магістерське дослідження розглядає динаміку поглиблення теоретико-методичних основ та удосконалення практичних рекомендацій щодо управління платоспроможністю підприємства. Розкрито економічну сутність та фактори впливу на платоспроможність підприємства; визначено методичні підходи до оцінки управління платоспроможністю підприємства; проаналізувати визначальні тенденції розвитку господарської діяльності підприємства ТОВ «Кондитерський цех» підприємства

The master's study examines the dynamics of deepening the theoretical and methodological foundations and improving practical recommendations for managing the company's solvency. The economic essence and factors affecting the solvency of the enterprise are disclosed; methodical approaches to the assessment of enterprise solvency management are defined; to analyze the determining trends in the development of the economic activity of the enterprise LLC "Confectionery shop" of the enterprise
Enterprise solvency management according to the materials of LLC "Confectionery shop»
Keywords: платоспроможність; управління; ефективність; ліквідність; фінансова стійкість; solvency; management; efficiency; liquidity; financial stability